2014
DOI: 10.1111/jace.13361
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen on Properties of Na2O–CaO–SrO–ZnO–SiO2 Glasses

Abstract: Glasses in the Na 2 O-CaO-SrO-ZnO-SiO 2 system have previously been investigated for suitability as a reagent in Al-free glass polyalkenoate cements (GPCs). These materials have many properties that offer potential in orthopedics. However, their applicability has been limited, to date, because of their poor strength. This study was undertaken with the aim of increasing the mechanical properties of a series of these Zn-based GPC glasses by doping with nitrogen to give overall compositions of: 10Na 2 O-10CaO-20S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…The increase in Tg with N is consistent with previous studies of oxynitride glasses [12][13][14][15][16][17][18] which have shown that N creates extra cross-linkages and stiffens the glass network [33].…”
Section: Glass Transition Temperature Tgsupporting
confidence: 91%
See 2 more Smart Citations
“…The increase in Tg with N is consistent with previous studies of oxynitride glasses [12][13][14][15][16][17][18] which have shown that N creates extra cross-linkages and stiffens the glass network [33].…”
Section: Glass Transition Temperature Tgsupporting
confidence: 91%
“…For oxynitride glasses (without fluorine), the slope is somewhat lower but this was thought to be due to the presence of bubbles in the glass. The benefit of nitrogen seems to be similar for the glasses studied here and bioactive glasses containing nitrogen which have been previously reported [14,17,18,22,23].…”
Section: Fig 7: Young's Modulus Of Na-ca-p-si-o-n Glasses As a Functi...supporting
confidence: 85%
See 1 more Smart Citation
“…For example, the reduction of oxides such as Li 2 O, Al 2 O 3 , MgO, CaO, and BaO by Si 3 N 4 is not thermodynamically feasible in the usual temperature range of syntheses, in opposition to Na 2 O, P 2 O 5 , K 2 O, Cs 2 O, and ZnO. 5,88,72,108,109 Nevertheless, this reduction is sometimes observed via an exothermic reaction in the form of vapors. 37 However, let us recall that such a tool brings no information about the kinetics.…”
Section: Side Reactionsmentioning
confidence: 99%
“…However, the low mechanical strength and inherent brittleness of these bioglasses have restricted their use to non-load-bearing applications [15] such as ossicles in the middle ear. The incorporation of nitrogen into the silicate network has been proposed as solution to resolve the problem of low strength in glasses [16,17] .…”
Section: Introductionmentioning
confidence: 99%